MR Findings of Decerebrate Rigidity with Preservation of Consciousness - Kao, C.-D.; Guo, W.-Y.; Chen, J.-T.; Wu, Z.-A.; Liao, K.-K. (American Journal of Neuroradiology, 2006)
SUMMARY: We describe a case of decerebrate rigidity, with preservation of consciousness, caused by a discrete pontine tegmentum lesion identified on MR imaging. Lesions within a certain brain stem region are responsible for decerebrate rigidity in animal studies, but there has been a lack of MR imaging evidence in humans. This report also implies that a discrete lesion was responsible for the decerebrate rigidity, while consciousness was preserved.